HMGA1 negatively regulates NUMB expression at transcriptional and post transcriptional level in glioblastoma stem cells. Issue 13 (3rd July 2019) - Puca, Francesca; Tosti, Nadia; Federico, Antonella; Kuzay, Yalçın; Pepe, Anna; Morlando, Sonia; Savarese, Teresa; D'Alessio, Federica; Colamaio, Marianna; Sarnataro, Daniela; Ziberi, Sihana; De Martino, Marco; et al.
ABSTRACT: Glioblastoma (GBM) is a lethal, fast-growing brain cancer, affecting 2–3 per 100, 000 adults per year. It arises from multipotent neural stem cells which have reduced their ability to divide asymmetrically and hence divide symmetrically, generating increasing number of cancer stem cells, fostering tumor growth. We have previously demonstrated that the architectural transcription factor HMGA1 is highly expressed in brain tumor stem cells (BTSCs) and that its silencing increases stem cell quiescence, reduces self-renewal and sphere-forming efficiency in serial passages, suggesting a shift from symmetric to asymmetric division. Since NUMB expression is fundamental for the fulfillment of asymmetric division in stem cells, and is lost or reduced in many tumors, including GBM, we have investigated the ability of HMGA1 to regulate NUMB expression. Here, we show that HMGA1 negatively regulates NUMB expression at transcriptional level, by binding its promoter and counteracting c/EBP-β and at posttranscriptional level, by regulating the expression of MSI1 and of miR-146a. Finally, we report that HMGA1 knockdown-induced NUMB upregulation leads to the downregulation of the NOTCH1 pathway. Therefore, the data reported here indicate that HMGA1 negatively regulates NUMB expression in BTSCs, further supporting HMGA1 targeting as innovative and effective anti-cancer therapy.